The Effectiveness of Problem Based Learning Method towards Student’s Critical Thinking Skills in Argumentative Essay Writing - Alifatun Nikmah (JEET, Journal of English Education and Technology, 2022)
This research is focused on investigating the effectiveness of Problem Based Learning toward students Critical Thinking skills Argumentative Essay Writing ability of second grade students of MA Raudlatul Muta’allimin Babat Lamongan. It is based on the analysis of the data that gained from the students which related to the teaching writing. The method uses Quantitative approach by using test to know the students competences before and after experiment run. There are two kinds of test were given to the students, they are pre-test and post-test. Before items of the test given to the students, the researcher give try out test to analyze the validity and reliability of each item. It shows that an independent t test from the problem based learning method toward critical thinking, the result was 3,13, the result of independent sample t test from the Problem Based Learning method toward argumentative essay writing was 8,66, and the result from One–Way ANOVA analysis of Problem-Based Learning method toward Critical Thinking and Argumentative Essay Writing showed the score was 5,23. The independent t test from both analyzes were higher than t table with level of significant 5% = 2,032 and the result of One-Way ANOVA was 5,23 higher than F table with level of significant 5% = 4,10. Which mean the Ha from t test and ANOVA are accepted. So using Problem-Based Learning methods in teaching writing have a significant effect towards the students Critical Thinking and Argumentative Essay Writing